Réponses

2014-01-03T12:09:04+01:00
1) (8x+7)2 -2(x+3)(8x+7)=
= 64x2 +8x*2*7+49 - 2( 8x2+ 7x+ 24x+21=
= 64x2+112x+48-2(8x2+31x+21)=
=64x2+112x+48-16x2-62x-42=
=48x2+50x+6

2)
1) (8x+7)² -2(x+3)(8x+7)=
= 64x² +8x*2*7+49 - 2( 8x²+ 7x+ 24x+21=
= 64x²+112x+49-2(8x²+31x+21)=
=64x²+112x+49-16x²-62x-42=
=48x²+50x+7

2)(8x+7)²-2(x+3)(8x+7)=
=(8x+7)(8x+7)-2(x+3)(8x+7)=
=(8x+7)(8x+7-2(x+3))=
=(8x+7)(8x+7-2x-6)=
=(8x+7)(6x+1)
3)(8x+7)(6x+1)=
=(8x*6x+8x*1+7*6x+7*1)=
=(48x²+8x+42x+7)=
=48x²+50x+7

4)(8x+7)(6x+1)=0
(8x+7)=0 ou (6x+1)=0
=8x=-7= =6x=-1 donc S= ( -7/8; -1/6)
=x=-7/8 =x=-1/6
5) (8x+7)(6x+1)= (8x+7)(6x+1)=
=(8*(-2)+7)(6*(-2)+1)= =(8*√3+7)(6*√3+1)=
=(-16+7)(-12+1)= =
=-9*(-11)=
=-99
(8x+7)(6x+1)=
=(8*1/6+7)(6*1/6+1)=
=(8/6+7)(6/6+1)=
=(8/6+42/6)(1+1)=
=50/6+1=
=50/6+6/6=
=56/6
=28/3